2010
DOI: 10.1159/000314708
|View full text |Cite
|
Sign up to set email alerts
|

The International Consortium on Lithium Genetics (ConLiGen): An Initiative by the NIMH and IGSLI to Study the Genetic Basis of Response to Lithium Treatment

Abstract: For more than half a decade, lithium has been successfully used to treat bipolar disorder. Worldwide, it is considered the first-line mood stabilizer. Apart from its proven antimanic and prophylactic effects, considerable evidence also suggests an antisuicidal effect in affective disorders. Lithium is also effectively used to augment antidepressant drugs in the treatment of refractory major depressive episodes and prevent relapses in recurrent unipolar depression. In contrast to many psychiatric drugs, lithium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
99
0
5

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 148 publications
(104 citation statements)
references
References 58 publications
0
99
0
5
Order By: Relevance
“…Since then, it has been used as a first-line treatment of BPD and as prophylaxis to prevent its recurrence [99]. The rate of lithium treatment response [105] and prophylactic efficacy [39] in BPD is relatively high compared to placebo.…”
Section: Lithium Treatment For Bipolar Disordermentioning
confidence: 99%
See 1 more Smart Citation
“…Since then, it has been used as a first-line treatment of BPD and as prophylaxis to prevent its recurrence [99]. The rate of lithium treatment response [105] and prophylactic efficacy [39] in BPD is relatively high compared to placebo.…”
Section: Lithium Treatment For Bipolar Disordermentioning
confidence: 99%
“…The ConLi + Gen Consortium (www.ConLiGen.org) is an initiative by the National Institute of Mental Health (NIMH) and the International Group for the Study of Lithium-Treated Patients (IGSLI) (www.IGSLI.org) [99]. The ConLiGen has compiled genetic and clinical data from 3193 patients with BPD who had undergone lithium treatment in Europe, USA, Asia, and Australia [56].…”
Section: Collaborations To Study the Pharmacogenomics Of Lithiummentioning
confidence: 99%
“…Genetic factors and clinical characteristics contribute to the failure of a favourable treatment outcome [4,5]. A large number of genes are likely to influence the toxicity and response of an individual medication of antidepressant response [1][2][3][4][5][6][7][8][9][10][11][12][13][14]15]. A recent study focused on determination of the effect of the CYP2D6 genotype on the length of hospitalization stay for patients treated for major depressive disorder and found that the hospital stay was significantly longer in deficient CYP2D6 metabolizers compared with functional or supra-functional metabolizers [16].…”
Section: Current Findingsmentioning
confidence: 99%
“…Several genome scans and meta-analyses have been completed, mostly in international cooperation; others are on the way [52] . The genetic studies of lithium response have offered much promise and I cannot do justice to this exciting, quickly expanding area while staying within the assigned space.…”
Section: Search For Genetic Culpritsmentioning
confidence: 99%